Root surface areas of maxillary permanent teeth in anterior normal overbite and anterior open bite assessed using cone-beam computed tomography - Piyadanai Suteerapongpun (2018)
© 2017 by Korean Academy of Oral and Maxillofacial Radiology. Purpose: The aim of this study was to compare the root surface areas of the maxillary permanent teeth in Thai patients exhibiting anterior normal overbite and in those exhibiting anterior open bite, using cone-beam computed tomography (CBCT). Materials and Methods: CBCT images of maxillary permanent teeth from 15 patients with anterior normal overbite and 18 patients with anterior open bite were selected. Three-dimensional tooth models were constructed using Mimics Research version 17.0. The cementoenamel junction was marked manually. The root surface area was calculated automatically by 3-Matic Research version 9.0. The root surface areas of each tooth type from both types of bite were compared using the independent t-test (P < .05). The intraclass correlation coefficient was used to assess intraobserver reliability. Results: The mean root surface areas of the maxillary central and lateral incisors in individuals with anterior open bite were significantly less than those in those with normal bite. The mean root surface area of the maxillary second premolar in individuals with anterior open bite was significantly greater than in those with normal bite. Conclusion: Anterior open-bite malocclusion might affect the root surface area, so orthodontic force magnitudes should be carefully determined.